A history of macroeconomics from Keynes to Lucas and beyond - Vroey, Michel de (Cambridge : Cambridge University Press, 2015)
This book retraces the history of macroeconomics from Keynes's General Theory to the present. Central to it is the contrast between a Keynesian era and a Lucasian - or dynamic stochastic general equilibrium (DSGE) - era, each ruled by distinct methodological standards. In the Keynesian era, the book studies the following theories: Keynesian macroeconomics, monetarism, disequilibrium macroeconomics (Patinkin, Leijongufvud and Clower), non-Walrasian equilibrium models, and first-generation new Keynesian models. Three stages are identified in the DSGE era: new classical macroeconomics (Lucas), RBC modelling, and second-generation new Keynesian modeling. The book also examines a few selected works aimed at presenting alternatives to Lucasian macroeconomics. While not eschewing analytical content, Michel De Vroey focuses on substantive assessments, and the models studied are presented in a pedagogical and vivid yet critical way.
Title from publisher's bibliographic system (viewed on 01 Jan 2016).
Keywords: Macroeconomics -- History